A CLINIC IN THE “REAL” - Olivier, Bert (PINS-Psychology in Society, 2025)
Parker, I (2011) Lacanian psychoanalysis: Revolutions in subjectivity. London & New York: Routledge. ISBN 978-0-415-45543-5 pbk. Pages ix + 238. If Ian Parker’s published work has created a certain level of expectation in his readers, his latest book will not disappoint them. Not only does he come across as someone who “knows his Lacan” (and, incidentally, his Marx), but also – perhaps chiefly so here – as a knowledgeable, practicing Lacanian psychoanalyst, who is aware of the potential “therapeutic value” of analysis for analysands who are willing to confront their own alienation under capitalism, and in the process question their own understanding of, and relationship with, power. At the same time Parker is clearly someone who is under no illusion about any supposedly direct translation of the “return to themselves” of analysands under clinical conditions, into social and political action outside the clinic. No doubt his familiarity with Marx and Marxism is a contributing factor in this regard. His understanding of the relationship between the two kinds of “revolution”, alone, makes this book worth reading, and re-reading.